2020
DOI: 10.3390/rs12152381
|View full text |Cite
|
Sign up to set email alerts
|

Physics-based Bathymetry and Water Quality Retrieval Using PlanetScope Imagery: Impacts of 2020 COVID-19 Lockdown and 2019 Extreme Flood in the Venice Lagoon

Abstract: The recent PlanetScope constellation (130+ satellites currently in orbit) has shifted the high spatial resolution imaging into a new era by capturing the Earth’s landmass including inland waters on a daily basis. However, studies on the aquatic-oriented applications of PlanetScope imagery are very sparse, and extensive research is still required to unlock the potentials of this new source of data. As a first fully physics-based investigation, we aim to assess the feasibility of retrieving bathymetric and water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
64
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 61 publications
1
64
0
Order By: Relevance
“…Therefore, the focus of this study is on the exploration of 4-band PlanetScope imagery for surface water extraction and its accuracy assessment in the context of glacial lakes mapping and monitoring in the HKKH region. The PlanetScope imagery has previously been used in surface water mapping [18], water velocity computation [19], bathymetry [20,21] and benthic habitat monitoring [22]. Planet Labs offer limited free data access to researchers and academicians through their education and research program.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the focus of this study is on the exploration of 4-band PlanetScope imagery for surface water extraction and its accuracy assessment in the context of glacial lakes mapping and monitoring in the HKKH region. The PlanetScope imagery has previously been used in surface water mapping [18], water velocity computation [19], bathymetry [20,21] and benthic habitat monitoring [22]. Planet Labs offer limited free data access to researchers and academicians through their education and research program.…”
Section: Introductionmentioning
confidence: 99%
“…The current pandemic caused by the novel severe acute respiratory syndrome corona virus (SARS-COV2) and the coronavirus disease that first occurred in Wuhan, China, in late 2019 (COVID- 19) [1], has had a huge impact on modern societies [2][3][4][5][6][7][8][9][10][11] and changed human life dramatically in early 2020. Starting in Wuhan, China, in January 2020, several countries have imposed so-called "lockdowns" to parts or all of their territories.…”
Section: Introductionmentioning
confidence: 99%
“…During these lockdowns, private and social life as well as industrial and commercial activities were reduced to a minimum to break the exponential increase in the infection chain of the pandemic and reduce the strain on health systems and reduce the fatality rate accordingly. Besides the effects on the growth rates of virus infections [2,3], these lockdowns had several unintended effects [4][5][6][7][8][9][10][11]. These include a negative impact on the economy [4], on mental health and sleeping behavior [5] or the food intake of obese children [6], but also unintended positive effects on Measurements in 2020 were performed on 26 March, which was a few days after the start of the strongest lockdown in Germany.…”
Section: Introductionmentioning
confidence: 99%
“…8 ) according to satellite images is that Venice’s canals became clearer after one month of lockdown (ESA 2020b ). Niroumand-Jadidi et al ( 2020 ) reported an almost 50% reduction in total suspended matter (TSM) after lockdown using shallow-water inversion via Planet Scope imagery. Before the COVID-19 periods, the concentration of TSM was 3 g/m 3 on average; however, it was reduced to 1.4 g/m 3 during COVID-19 lockdown.…”
Section: Surface Water Quality and Wastewater Surveillancementioning
confidence: 99%